Advances in solubilization and stabilization techniques for structural and functional studies of membrane proteins - Zhou,Zhuanghan; Chen,Zheng; Li,Yiran; Mao,Xingyue; Chen,Junjie; Zhou,Xuan; Zhang,Bo (PeerJ, 2025)
Membrane proteins (MPs) are indispensable in various biological processes, including material transport, signal transduction, immune response, and cell recognition. Unraveling the intricate interplay between MP structure and function is pivotal for advancing fundamental biology and pharmaceutical research. However, the inherent hydrophobicity and complex lipid interactions of MPs pose significant challenges in determining their three-dimensional configurations. In recent years, cryo-electron microscopy (cryo-EM) has emerged as a powerful alternative for structural elucidation, overcoming the challenges faced by traditional techniques such as X-ray crystallography and nuclear magnetic resonance (NMR). This review centers on advanced solubilization and stabilization techniques for MPs, as well as MP functions and expression systems, highlighting the strengths and limitations of conventional detergents, liposomes, bicelles, and nanodiscs, alongside emerging alternatives like styrene-maleic acid (SMA) and diisobutylene-maleic acid (DIBMA). Notably, SMA and its derivatives provide promising detergent-free alternatives that preserve protein stability and native conformation, which is particularly valuable for accurate cryo-EM characterization of complex MPs. This work is designed to serve as both an updated resource for researchers already immersed in the field and an accessible entry point for those new to MP research. By consolidating recent advancements and highlighting critical gaps, this review aims to inspire future investigations that push the boundaries of MP structural and functional studies, ultimately driving innovations in drug discovery and therapeutic development.
Keywords: Membrane protein; Membrane solubilization; Detergent-free extraction; SMA; DIBMA